Risk Factors for Incident Myopia among Teenaged Students of the Experimental Class of the Air Force in China - Lin-song Qi; Lu Yao; Xue-feng Wang; Jiu-mei Shi; Yong Liu; Teng-yun Wu; Zhi-kang Zou (Journal of Ophthalmology)
Background. In recent decades, the prevalence rate of myopia has markedly increased, especially among teenagers. Our purpose was to determine the incidence of myopia and identify the related risk factors among schoolchildren in the experimental classes of the Air Force in China. Methods. In May 2015, this 3-year prospective cohort study enrolled 522 boys (age, 14–16 years) attending grade 10 in 16 high schools in 15 cities in China. Cycloplegic refraction was examined using retinoscopy in both eyes at the baseline and follow-up (3 years). A detailed questionnaire was completed by the students at the 3-year follow-up and included questions on parental myopia and on the total time spent doing near work and outdoor activities each week. Results. The incidence of myopia at the 3-year follow-up was 27.01% (141/522, 95% confidence interval (CI): 23.38% to 30.98%). The refractive change was −0.46 D (95% CI: −0.49 to −0.42 D). More hyperopic or less myopic baseline refraction, outdoor activity time per week ≥14 h (odds ratio (OR) = 0.464, 95% CI: 0.227 to 0.950), and reading/writing distance ≥ 30 cm (OR = 0.505, 95% CI: 0.270 to 0.944) were significant protective factors against incident myopia. Near-work time ≥28 h per week was a significant risk factor (OR = 2.579, 95% CI: 1.314 to 5.061). Parental myopia, age at the start of primary school, continuous reading/writing for ≥1 h, sleep duration per week <49 h, and one or more dietary biases were not significant risk factors (P>0.05). Conclusion. A more hyperopic baseline refraction, more time spent outdoors, and longer writing/reading distance were protected against myopia onset, while more near-work time was a risk factor.